2023
DOI: 10.3390/s23094178
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Machine Learning in Healthcare Industry: Classification, Restrictions, Opportunities and Challenges

Abstract: Recently, various sophisticated methods, including machine learning and artificial intelligence, have been employed to examine health-related data. Medical professionals are acquiring enhanced diagnostic and treatment abilities by utilizing machine learning applications in the healthcare domain. Medical data have been used by many researchers to detect diseases and identify patterns. In the current literature, there are very few studies that address machine learning algorithms to improve healthcare data accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…With the advent of natural language processing (NLP) and machine learning (ML) models in healthcare since the late 1990s [13], delirium risk can now be predicted with 94.1% accuracy in geriatric internal medicines inpatients [14]. Building accurate predictive models based on logistic regression algorithm is widely used in the medical field [15] with Generative AI now offering an opportunity to augment and accompany the output compared against these logistic regression models [16,17]. As a result, several logistic regressions, machine learning-based delirium prediction models have been developed since 2018 [18][19][20][21][22][23][24].…”
Section: Evolution Of Llmsmentioning
confidence: 99%
“…With the advent of natural language processing (NLP) and machine learning (ML) models in healthcare since the late 1990s [13], delirium risk can now be predicted with 94.1% accuracy in geriatric internal medicines inpatients [14]. Building accurate predictive models based on logistic regression algorithm is widely used in the medical field [15] with Generative AI now offering an opportunity to augment and accompany the output compared against these logistic regression models [16,17]. As a result, several logistic regressions, machine learning-based delirium prediction models have been developed since 2018 [18][19][20][21][22][23][24].…”
Section: Evolution Of Llmsmentioning
confidence: 99%
“…In the last decade, machine learning (ML) algorithms have been widely used in clinical prediction models to aid in early disease prediction, severity grading, classification, and prognostication of patients. Compared with conventional logistic regression, ML can effectively handle complex linear and nonlinear relationships among variables in large datasets, resulting in superior predictive performance (14)(15)(16)(17). While several studies have investigated the risk factors and prediction models for IFI (18)(19)(20)(21)(22)(23)(24)(25)(26), existing models often suffer from limitations such as small sample sizes, focusing on a single fungal infection, or utilizing features that are difficult to obtain in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Although traditional machine learning techniques have gradually become the core means of mining the deep value of medical big data, and have made breakthroughs in the accurate diagnosis of diseases 1 , prospective prediction of patient treatment response, and formulation of individualised treatment strategies 2 . However, conventional machine learning methods have revealed a series of inherent limitations when applied to complex medical data like hepatitis C. An et al 3 found that conventional machine learning techniques are difficult to effectively mine the non-linear, high-dimensional pathophysiological patterns hidden in highly complex medical data containing multiple clinical indicators and biomarker information. Meanwhile, Rahman et al 4 suggested the prevalent category imbalance problem in medical datasets leads traditional machine learning models to be ineffective in dealing with rare and early-stage conditions, and to face significant challenges in terms of robustness and generalisation when coping with situations such as high noise, large amounts of missing data and outliers.…”
Section: Introductionmentioning
confidence: 99%